Place Marketing in Hungary: The Case of Debrecen - Kozma, Gábor (European Spatial Research and Policy, 2009)
After the political transformations in East-Central Europe local authorities were forced to realise that they have to employ more active policy, and consequently, the use of place marketing became more popular. The study examines one particular city in Hungary, Debrecen, and concentrates on two areas. First, it presents what methods were employed in an attempt to attract economic players and tourists, and to increase the satisfaction of existing target groups. Secondly, it evaluates the steps taken: how characteristic were the tools used in Debrecen in other Hungarian cities, and what positive and negative features of marketing activity can be identified.